Expressões de gênero no desenho infantil - Montagna, Adelma Pistun (2001)
Effects a triple look at the development of the children’s drawing based on the perspectives that can be found in the studies of Moreira, Lowenfeld e Luquet. Aimed at observing drawings produced by infant males and females in a private elementary education school in downtown Londrina, it identifies, by the means of expressed repertory, how gender issues will appear among them. A children’s education study on gender, the investigation seeks to uncover particular elements of a kaleidoscope of expression possibilities. Having as its main assumption the idea that sexual roles and gender identification are social constructs and that, moreover, the ways of looking at and interpreting reality are direct produces of a determined time and space, it effectively found differences between male and female drawings.